Mitochondrial tRNA-Derived Fragments and Their Contribution to Gene Expression Regulation - Shaukat, Athanasios-Nasir; Kaliatsi, Eleni G.; Stamatopoulou, Vassiliki; Stathopoulos, Constantinos (Frontiers in Physiology, 2021)
Mutations in human mitochondrial tRNAs (mt-tRNAs) are responsible for several and sometimes severe clinical phenotypes, classified among mitochondrial diseases. In addition, post-transcriptional modifications of mt-tRNAs in correlation with several stress signals can affect their stability similarly to what has been described for their nuclear-encoded counterparts. Many of the perturbations related to either point mutations or aberrant modifications of mt-tRNAs can lead to specific cleavage and the production of mitochondrial tRNA-derived fragments (mt-tRFs). Although mt-tRFs have been detected in several studies, the exact biogenesis steps and biological role remain, to a great extent, unexplored. Several mt-tRFs are produced because of the excessive oxidative stress which predominantly affects mitochondrial DNA integrity. In addition, mt-tRFs have been detected in various diseases with possible detrimental consequences, but also their production may represent a response mechanism to external stimuli, including infections from pathogens. Finally, specific point mutations on mt-tRNAs have been reported to impact the pool of the produced mt-tRFs and there is growing evidence suggesting that mt-tRFs can be exported and act in the cytoplasm. In this review, we summarize current knowledge on mitochondrial tRNA-deriving fragments and their possible contribution to gene expression regulation.